2002
DOI: 10.1002/1521-4141(200201)32:1<67::aid-immu67>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Secretory phospholipases A2 induce cytokine release from blood and synovial fluid monocytes

Abstract: Secretory phospholipases A2 (sPLA2) are released in the blood of patients with various inflammatory diseases and exert proinflammatory activities by releasing arachidonic acid (AA), the precursor of eicosanoids. We examined the ability of four sPLA2 to activate blood and synovial fluid monocytes in vitro. Monocytes were purified from blood of healthy donors or from synovial fluid of patients with rheumatoid arthritis by negative immunoselection and by adherence to plastic dishes, respectively. The cells were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 52 publications
2
44
0
1
Order By: Relevance
“…In three experiments, at a concentration of 10 g/ml, hGX and bvGIII, but not hGIB, induced the release of a significant amount of AA from HLM (percentage of total cellular [ 3 H]AA released in 1 h: hGIB, 3.1 Ϯ 0.7%; bvGIII, 6.0 Ϯ 1.1% ( p Ͻ 0.05 vs unstimulated); hGX, 6.6 Ϯ 1.1 ( p Ͻ 0.05 vs unstimulated); unstimulated, 2.9 Ϯ 0.5). These results are in line with earlier studies showing that hGX and bvGIII, which bind to the extracellular face of mammalian cell membranes, but not hGIB, efficiently release [ 3 H]AA when added exogenously to intact mammalian cells (36,41,44). Our data demonstrate that the capacity of each sPLA 2 to mobilize AA in macrophages is unrelated to their ability to induce cytokine production.…”
Section: Role Of Spla 2 Enzymatic Activity In Cytokine Production Frosupporting
confidence: 93%
See 3 more Smart Citations
“…In three experiments, at a concentration of 10 g/ml, hGX and bvGIII, but not hGIB, induced the release of a significant amount of AA from HLM (percentage of total cellular [ 3 H]AA released in 1 h: hGIB, 3.1 Ϯ 0.7%; bvGIII, 6.0 Ϯ 1.1% ( p Ͻ 0.05 vs unstimulated); hGX, 6.6 Ϯ 1.1 ( p Ͻ 0.05 vs unstimulated); unstimulated, 2.9 Ϯ 0.5). These results are in line with earlier studies showing that hGX and bvGIII, which bind to the extracellular face of mammalian cell membranes, but not hGIB, efficiently release [ 3 H]AA when added exogenously to intact mammalian cells (36,41,44). Our data demonstrate that the capacity of each sPLA 2 to mobilize AA in macrophages is unrelated to their ability to induce cytokine production.…”
Section: Role Of Spla 2 Enzymatic Activity In Cytokine Production Frosupporting
confidence: 93%
“…Macrophages were incubated (6 h, 37°C) with increasing concentrations (0.1-10 g/ml) of hGIB or hGX and with bvGIII, an isoform that does not induce TNF-␣ and IL-6 production from human blood monocytes (41). Both hGIB and hGX induced a concentration-dependent release of TNF-␣ and IL-6 (Fig.…”
Section: Effects Of Spla 2 S On Tnf-␣ and Il-6 Release From Hlmmentioning
confidence: 97%
See 2 more Smart Citations
“…Clearly this does not exclude the potential implication of an indirect effect via modifications of the immune system per se, particularly through the interaction with a receptor on certain cell types (40). Several studies with various sPLA 2 s, including human group IIA, have shown that these sPLA 2 s can trigger iNOS induction (41), COX-2 induction (42) and IL-6, IL-8, and TNF-␣ cytokine secretion (43), through a mechanism involving ERK1/2 (41,44). However, in our study, sPLA 2 -IIA was found effective even against infection with a B. anthracis strain secreting the toxins that are known to block the MAPK cascade (ERK/P38) through MEK cleavage (45,46); this observation suggests a predominant direct bactericidal effect.…”
Section: Discussionmentioning
confidence: 99%